2014
DOI: 10.1007/s00595-014-0834-3
|View full text |Cite
|
Sign up to set email alerts
|

Aortoenteric fistula at the site of esophagojejunostomy after laparoscopic total gastrectomy: report of a case

Abstract: A fistula between the aorta and the digestive tract is a rare complication of gastrointestinal tract or vascular surgery. There are occasional reports of aortoesophageal fistula as a fatal complication after esophagectomy or esophageal stent implantation and of aortoenteric fistula (AEF) as a complication after aortic or other vascular procedures. However, AEF after gastrointestinal surgery is rare. We report a case of AEF after laparoscopic total gastrectomy for advanced gastric cancer, using the so-called ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Overlap esophagojejunostomy has been reported to be a safe and useful technique in laparoscopic total gastrectomy [13, 8]. Gunji et al reported a case of AEF after laparoscopic total gastrectomy with overlap esophagojejunostomy for advanced gastric cancer with esophageal invasion [6]. In the reported case, bacterial peritonitis was diagnosed 5 days after the operation, manifesting as partial necrosis and perforation of the small intestine.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Overlap esophagojejunostomy has been reported to be a safe and useful technique in laparoscopic total gastrectomy [13, 8]. Gunji et al reported a case of AEF after laparoscopic total gastrectomy with overlap esophagojejunostomy for advanced gastric cancer with esophageal invasion [6]. In the reported case, bacterial peritonitis was diagnosed 5 days after the operation, manifesting as partial necrosis and perforation of the small intestine.…”
Section: Discussionmentioning
confidence: 96%
“…Noshiro stated that some extraverted esophageal and intestinal stumps in the thorax should be covered by suturing to prevent the formation of pulmonary fistulas, although AEF was not mentioned [5]. Gunji et al reported an AEF located above a triangular anastomosis between the esophagus, jejunal limb, and the descending aorta [6]. They speculated that the persistent contact of the staple line eroded the aortic wall, leading to AEF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a case of aortoen-teric fistula at the esophagojejunostomy site after LTG for advanced gastric cancer located at the esophagogastric junction was reported. 12 Although two EPF cases associated with open total gastrectomy for gastric cancer have been reported, 3,4 there have been no reports of EPF induced by LTG for gastric cancer. To the best of our knowledge, our case is the first report of an EPF induced by LTG for gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There are occasional reports of aortoesophageal fistula after esophagectomy or esophageal stenting. However, aortoenteric fistula after gastrointestinal surgery is rarely seen [Gunji 2014].…”
Section: E24mentioning
confidence: 99%